Newly divided eosinophils limit ozone-induced airway hyperreactivity in nonsensitized guinea pigs - Wicher, Sarah A.; Jacoby, David B.; Fryer, Allison D. (American journal of physiology. Lung cellular and molecular physiology, 2017)
Ozone causes vagally mediated airway hyperreactivity and recruits inflammatory cells, including eosinophils, to lungs, where they mediate ozone-induced hyperreactivity 1 day after exposure but are paradoxically protective 3 days later. We aimed to test the role of newly divided eosinophils in ozone-induced airway hyperreactivity in sensitized and nonsensitized guinea pigs. Nonsensitized and sensitized guinea pigs were treated with 5-bromo-2-deoxyuridine (BrdU) to label newly divided cells and were exposed to air or ozone for 4 h. Later (1 or 3 days later), vagally induced bronchoconstriction was measured, and inflammatory cells were harvested from bone marrow, blood, and bronchoalveolar lavage. Ozone induced eosinophil hematopoiesis. One day after ozone, mature eosinophils dominate the inflammatory response and potentiate vagally induced bronchoconstriction. However, by 3 days, newly divided eosinophils have reached the lungs, where they inhibit ozone-induced airway hyperreactivity because depleting them with antibody to IL-5 or a TNF-α antagonist worsened vagally induced bronchoconstriction. In sensitized guinea pigs, both ozone-induced eosinophil hematopoiesis and subsequent recruitment of newly divided eosinophils to lungs 3 days later failed to occur. Thus mature eosinophils dominated the ozone-induced inflammatory response in sensitized guinea pigs. Depleting these mature eosinophils prevented ozone-induced airway hyperreactivity in sensitized animals. Ozone induces eosinophil hematopoiesis and recruitment to lungs, where 3 days later, newly divided eosinophils attenuate vagally mediated hyperreactivity. Ozone-induced hematopoiesis of beneficial eosinophils is blocked by a TNF-α antagonist or by prior sensitization. In these animals, mature eosinophils are associated with hyperreactivity. Thus interventions targeting eosinophils, although beneficial in atopic individuals, may delay resolution of airway hyperreactivity in nonatopic individuals.